Corrosion science and technology - Talbot, David E. J. (CRC Press, 2007)
The authors discuss the nature of metallic structures and measures that can be taken to arrest or suppress the degradation of engineering metals. Topics include the use of protective coatings; attributes and corrosion behavior of plain carbon steels and irons, stainless steels, and aluminum alloys; and practical implications for such total technologies as aviation, automobile manufacture, food handling, and building construction.